(untitled) (Research, Society and Development, 2022)
Verification for the efficiency of the neurotransmitter serotonin for neurological diseases and disorders, has granted relevant in the study of the nervous system, given that serotonin releases the feeling of welfare state. However, 5- hydroxtryptamine was related to the nutritional part of individuals with the diseases studied, thus, a joint work was carried out to benefit them. Objective: to investigate and understand the neurotransmitter serotonin in alimentary inssues as improviment for mental illness and disorders. Methodology: This is a systematic review based on the analysis of 28 articles from the years 2011 to 2020 on Scielo and BVS, plus books from the physiology, psychopharmacology, anatomy and nutrition. In view of this, the obtained results hás shwon that the serotonergic system together with nutrition issues helps in the treatment of depression, ASD, ADHD, SZC and AD. Conclusion: Serotonin acting on addition with food had shown to be effective in improving mental health. In this way, maintaining a diet conducive to brain health for the correct production of serotonin is an important factor for combat and prevention.